2012
DOI: 10.1080/10941665.2011.625430
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Malaysian Tourism and Hospitality Students' towards a Career in the Industry

Abstract: This study explored Malaysian undergraduate tourism and hospitality students' views of the industry as a career choice. Four hundred and twenty-nine tourism and hospitality students, from three Malaysian institutions completed a questionnaire rating the importance of 20 factors in influencing their choice of career, and then the extent to which they believed tourism and hospitality as a career offers these factors. All of the 20 factors tested have been identified as being significantly different. From the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 32 publications
7
64
1
7
Order By: Relevance
“…He found that the students did not believe that the tourism and hospitality industry could offer them these factors, the five most important being 'A job that I will find enjoyable'; 'Pleasant working environment'; 'A secure job'; 'Colleagues that I can get along with'; and 'High earnings over a length of time'. Two other studies on tourism and hospitality students' perceptions of a career in the industry showed the same results, indicating that the students did not believe that the industry will offer them what they find important when choosing a career (Richardson & Butler, 2012;Richardson & Thomas, 2012). Dagsland et al (2011) studied apprentices' expectations of and experiences in their encounter with the hospitality industry.…”
Section: Conceptual Framework and Literature Reviewsupporting
confidence: 49%
See 1 more Smart Citation
“…He found that the students did not believe that the tourism and hospitality industry could offer them these factors, the five most important being 'A job that I will find enjoyable'; 'Pleasant working environment'; 'A secure job'; 'Colleagues that I can get along with'; and 'High earnings over a length of time'. Two other studies on tourism and hospitality students' perceptions of a career in the industry showed the same results, indicating that the students did not believe that the industry will offer them what they find important when choosing a career (Richardson & Butler, 2012;Richardson & Thomas, 2012). Dagsland et al (2011) studied apprentices' expectations of and experiences in their encounter with the hospitality industry.…”
Section: Conceptual Framework and Literature Reviewsupporting
confidence: 49%
“…Yet, previous research (e.g., Getz, 1994;Jenkins, 2001;Kusluvan & Kusluvan, 2000;Richardson, 2009Richardson, , 2010Richardson & Butler, 2012;Richardson & Thomas, 2012;Ross, 1991) on the perceptions and attitudes of young people toward work in the industry has mainly been carried out among high school students and even more frequently among undergraduates already enrolled in an educational program within the field. Consequently, these studies may only answer the call in relation to students who are already enrolled in hospitality courses.…”
Section: Introductionmentioning
confidence: 99%
“…The hospitality sector in Malaysia needs to focus on human resource awareness training and satisfaction to achieve work loyalty. Delivering high quality service can lead to re-visit in the future (Foong-ming, 2008;Richardson & Butler, 2011).…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Roney ve Öztin'in (2007) Türkiye'nin üç faklı üniversitesinde yaptıkları kariyer algısı belirleme çalışmasında, öğrencilerin çoğunluğunun turizm eğitiminin doğru bir kariyer tercihi olduğunu ve bu yolla iyi paralar kazanılabileceğini düşündüklerini ortaya koymuştur. Chuang ve Jenkins'in (2010) Öğrencilerin sektöre karşı olumsuz tutumlarının en önemli nedenleri işin stresli olması, aile yaşantısını olumsuz etkilemesi, sektördeki uzun ve yorucu çalışma saatleri, işin sezonluk olması, işin sosyal statüsünün düşük olması, ücretin ve yan gelirlerin düşük olması, terfi imkanlarının kısıtlı olması, verilen eğitimin bu karmaşık sektörde başarılı olmak için yetersiz olması, iş güvencesi ve çalışma garantisi olmaması, eğitimsiz işgörenler ve yöneticiler, yöneticilerin işgörenlere karşı kötü davranışları ve kötü fiziksel koşullardır (Kuşluvan ve Kuşluvan, 2000;Birdir, 2002;Öztürk ve Pelit, 2008;Jiang ve Tribe, 2009;Richardson ve Butler, 2012).…”
Section: Li̇teratürunclassified